1999
DOI: 10.1002/(sici)1522-2594(199905)41:5<992::aid-mrm19>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor microscopy of the intervertebral disc anulus fibrosus

Abstract: Morphologically accurate biomechanical models of the intervertebral disc anulus fibrosus (AF) require precise knowledge of its lamellar architecture; however, available methods of assessment are limited by poor spatial resolution or the destructive nature of the technique. In a novel approach, diffusion tensor microscopy was used in this study to characterize the microstructure of excised porcine AF samples. Results show diffusion in the AF to be anisotropic. The orientations of anisotropy exhibit a layered mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 27 publications
3
40
0
Order By: Relevance
“…Similar quantitative imaging studies investigating intervertebral disc degeneration have been performed previously, including T 1 -and T 2 -weighted relaxation [4,8,11], magnetization transfer [27], diffusion imaging [3,15,18,21], and spectroscopy [19,22]. Some techniques, while appropriate for basic science research, are less suitable for clinical in vivo applications.…”
Section: Discussionmentioning
confidence: 86%
“…Similar quantitative imaging studies investigating intervertebral disc degeneration have been performed previously, including T 1 -and T 2 -weighted relaxation [4,8,11], magnetization transfer [27], diffusion imaging [3,15,18,21], and spectroscopy [19,22]. Some techniques, while appropriate for basic science research, are less suitable for clinical in vivo applications.…”
Section: Discussionmentioning
confidence: 86%
“…Quantitative T 1r imaging has been used in cartilage (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) and is affected by the interaction between motionally restricted water molecules and their macromolecular environment such as the glycosaminoglycan content. The extracellular matrix in the intervertebral disc may potentially be investigated using these techniques.…”
Section: Mri Relaxation Time Measurementsmentioning
confidence: 99%
“…It was also shown that collagenase degradation of the nucleus slightly increased the apparent diffusion coefficient (ADC) (36). In a microscopic diffusion tensor study (37), at 7.1 T, using specimens of porcine annulus fibrosus, Hsu et al demonstrated diffusion anisotropy, which potentially could be related to the collagen fiber orientation.…”
Section: Mr Diffusion Measurementsmentioning
confidence: 99%
“…Previously applied to trace fibre tracts in the central nervous system [26,40,50] and study structure in cartilage [37] and skeletal muscle [3], the primary eigenvector of the diffusion tensor has been validated as a measure of cardiac fibre orientation [33,36,53] and the secondary and tertiary eigenvectors have been proposed as indices [61] and validated as measures [29] of ventricular sheet structure.…”
Section: Introductionmentioning
confidence: 99%